Development of Concurrent grinding for application in aqueous mineral carbonation. (1st March 2019) - Rashid, M.I.; Benhelal, E.; Farhang, F.; Oliver, T.K.; Rayson, M.S.; Brent, G.F.; Stockenhuber, M.; Kennedy, E.M.
Abstract: Vast reserves of peridotite and serpentinite rocks can be utilised for the safe and permanent sequestration of global CO2 emissions via aqueous mineral carbonation. These, and indeed most feedstocks used in mineral carbonation require ultrafine grinding and/or heat-activation, to engender significantly enhanced reactivity in the rock such that it can then be carbonated. Both activation processes are energy intensive and present significant obstacles to the commercial application of mineral carbonation. Here we show that these limitations can be addressed, at least in part, through the application of a concurrent or in operando grinding technique which does not require feedstocks which have been subjected to prior ultrafine grinding nor heat-activation. Concurrent grinding is shown to result in a significant increase in magnesite yields for non-heat activated feedstock, prepared such that fines (<20 μm particles) were excluded from the feed. We assert that concurrent grinding may be a suitable technique for the processing of feedstocks such as those containing significant proportions of forsterite and pyroxene, minerals which are unresponsive to thermal activation for use in aqueous mineral carbonation. This study also investigates the effect of different grinding media particle size on reducing the particle size distribution (PSD) of the feed. Optimum ratio of grinding media size to feed particle size, optimum grinding media and slurry concentrations, optimum time for grinding and optimum impeller designs are determined for the system under study. The quantitative effect of grinding media concentration, slurry concentration, pressure and temperature on magnesite yield has been investigated. Highlights: Feedstocks can be carbonated using concurrent grinding without prior pre-treatment. Different grinding medias and media mixtures were investigated. Different impeller designs were investigated. Quantitative effect of operating variables was determined. 62% magnesite yield was obtained using raw dunite rock.